The effects of vertebral rotation on the position of the aorta relative to the spine in patients with adult degenerative scoliosis - Yan Liang; Shuai Xu; Yongfei Zhao; Haiying Liu; Keya Mao (SAGE Publishing, 2021)
Aims: This study aimed to explore the effects of vertebral rotation on the position of the aorta relative to the thracolumbar and lumbar spine, and to identify risk factors for vertebral rotation in patients with adult degenerative scoliosis (ADS). Methods: A total of 71 patients with ADS were divided into left scoliosis (LS) group ( n  = 40 cases) and right scoliosis (RS) group ( n  = 31cases) with well-matched demographics. Apical vertebrae, Cobb angle (°), coronal horizontal movement, thoracolumbar kyphosis (TLK) and Nash-Moe rotation classification were measured on X-ray. The Cartesian coordinate system was established on T2-MRI for each level of intervertebral disc on thracolumbar and lumbar spine, where aorta-vertebrae angle (α), aorta-vertebrae distance (d), and vertebral rotation angle (γ) for each level of T12-L1 to L3-L4 on MRI were defined within the Cartesian coordinate system. Results: There was no statistical difference in the distribution of apical vertebrae between LS and RS groups. Nash-Moe classification was of no significance between the two groups. When there was a larger Cobb angle and coronal horizontal movement, a greater γ in LS group and a lower γ in RS group were noted (both p  < 0.001). There was no correlation among γ, α, and d in LS group ( p  = 0.908 and 0.661, respectively) nor in RS group ( p  = 0.738 and 0.289, respectively). In LS group, Nash-Moe classification correlated to Cobb angle, coronal movement and TLK. In RS group, it correlated to Cobb angle and coronal movement. Cobb angle was the risk factor for Nash-Moe classification in RS group while no factors were identified in LS group. Coronal movement was independent risk factor for γ ( p  = 0.003) in LS group. Moreover, γ was affected by Cobb angle ( p  = 0.001) and coronal horizontal movement ( p  = 0.006) in RS group. Conclusion: Vertebral rotation could be predicted by Cobb angle or coronal horizontal movement measured on X-ray in ADS patients and aorta maintained in a relatively normal position in patients with ADS.